Permeation of Weak Acids and Bases Through Lipid Bilayers – Modelling and Validation of a pH Variation Assay - Cordeiro, Margarida Machado (2022)
Dissertação de Mestrado em Química apresentada à Faculdade de Ciências e Tecnologia